2021
DOI: 10.3390/ijerph18084373
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Flavors and Frequency of E-Cigarette Use among Adult Dual Users Who Attempt to Quit Cigarette Smoking in the United States: Longitudinal Findings from the PATH Study 2015/16–2016/17

Abstract: Potential mechanisms by which e-cigarette use may relate to combustible cigarette smoking cessation are not well-understood. We used U.S. nationally representative data to prospectively evaluate the relationship between e-cigarette flavor use and frequency of e-cigarette use among adult cigarette/e-cigarette dual users who attempted to quit smoking cigarettes. Analyses used Population Assessment of Tobacco and Health (PATH) Study data from adult dual users (2015/16) who attempted to quit smoking between 2015/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“… 26 Other studies have reported an increase in the preference for cigarettes with flavor restrictions on e-cigarettes. 27 , 40 In contrast, Kasza et al 41 found no statistically significant differences in the rates of cigarette smoking quit attempts among dual users as a function of e-cigarette flavor use. Similarly, Meernik et al 42 found that non-menthol and tobacco flavors in e-cigarettes are a primary reason for adult cigarette smokers’ e-cigarette use, but that the role of flavored e-cigarettes on smoking cessation remains unclear.…”
Section: Discussionmentioning
confidence: 92%
“… 26 Other studies have reported an increase in the preference for cigarettes with flavor restrictions on e-cigarettes. 27 , 40 In contrast, Kasza et al 41 found no statistically significant differences in the rates of cigarette smoking quit attempts among dual users as a function of e-cigarette flavor use. Similarly, Meernik et al 42 found that non-menthol and tobacco flavors in e-cigarettes are a primary reason for adult cigarette smokers’ e-cigarette use, but that the role of flavored e-cigarettes on smoking cessation remains unclear.…”
Section: Discussionmentioning
confidence: 92%
“…Given the established importance of e-cigarette use frequency in cigarette smoking cessation behaviors, 2 , 3 , 4 it is important to understand associations of e-cigarette flavor types and device types with smoking cessation independent of any association these features may have with e-cigarette use frequency. Indeed, using US nationally representative data from the Population Assessment of Tobacco and Health (PATH) Study, Kasza et al 8 found that e-cigarette flavor and e-cigarette device type were each associated with e-cigarette use frequency among adults who used e-cigarettes and attempted to quit cigarette smoking; those who used sweet flavor e-cigarettes had higher use frequency than those who used tobacco flavor e-cigarettes, and those who used tank-style e-cigarettes had higher use frequency than those who used cartridge or disposable e-cigarettes. If use of sweet flavor, tank device types, or both are associated with greater cigarette cessation than use of other flavor and device types, then e-cigarette use frequency could be the mechanism underlying the association, which could explain why flavor and device type may be important in cigarette cessation.…”
Section: Introductionmentioning
confidence: 99%
“…Research has consistently demonstrated that flavours play a role among adults in ENDS initiation, continued use7 14–17 and facilitating switching from smoking to vaping 14. Adults use a wide range of flavours and commonly use non-tobacco flavoured ENDS 14–19. However, flavour preferences appear to differ by smoking status, where current smokers (dual users who smoke and vape) prefer tobacco flavours and ex-smokers (exclusive vapers) prefer fruit flavours 15 17 19.…”
Section: Introductionmentioning
confidence: 99%